STATUS OF PRO- AND ANTIOXIDANT SYSTEM OF RATS UNDER CONDITIONS OF ENERGY DRINK CONSUMPTION - Partsei, Kh.Yu.; Ersteniuk, H.M.; Shkurashivska, S.V.; Кindrat, I.P.; Senchiy, V.M. (World of Medicine and Biology, 2023)
The article is devoted to the study of the mechanism of the impact of energy drinks on the state of pro- and antioxidant system of erythrocytes of experimental animals. The study was carried out on male Wistar rats. We found that in the erythrocytes of experimental animals that consumed an energy drink for 30 days, the processes of free radical oxidation are activated, accompanied by the activation of lipo-peroxidation and peroxidation of proteins in experimental animals. Accumulation of the thiobarbituric acid active products and the content of diene conjugates can damage the lipid matrix of biomembranes, which in turn leads to disruption of the structural and functional capacity of erythrocyte cell membranes. High levels of protein carbonyl derivatives of erythrocytes may be due to disruption of both structural proteins and enzymes. Under such conditions, it is advisable to study the antioxidant defense of erythrocytes. The obtained results indicate an increase in catalase and superoxide dismutase activity in experimental animals compared with the control group, which may be due to the growth in the peripheral population of “early” forms of cells which are capable of active protein synthesis. This process can be considered as an adaptive synthesis of antioxidant enzymes. The study of the microelement status of rat erythrocytes under the conditions of energy consumption allowed to establish the development of dysmicroelementosis, which was accompanied by a decrease in the concentration of Copper and Ferrum.
Keywords: laboratory rats; energy drink; catalase; superoxide dismutase; TBK-active products; diene conjugates oxidative modification of proteins